Development of Mathematics Comic Learning Media for Students of Class VII SMP/MTs Based On Culture - Yuli Fitrianingsih; Huri Suhendri; Maya Masitha Astriani (JURNAL PETIK, 2019)
This study aims to develop a culture-based mathematics comic learning media using research and development or R & D methods with the ASSURE model. This development research was conducted in three Junior High Schools (JHS) in one sub-district, Pasar Minggu sub-district, South Jakarta. This research has been tested to various experts, namely: two material experts with very good categories and a percentage of 86%, 72% from one linguist with a good category, 96% from one development expert with a very good category, and get a percentage 3,4 with a good category from one graphic design expert. While the results of one to one test evaluations get an average of 84% which falls into the good category, small group test with a percentage of 85% with a very good category, and a large group test using the t-test results obtained tcount > ttable. Based on the evaluation results from several experts, using learning media in the form of mathematical comics is considered feasible and can increase students' interest and learning outcomes.